Photonic properties of pzt powders along the crystallization process of the polymeric precursor - da Silva, Margarete Soares; de Souza, Eliane Ferreira; Ramos, Talita Cuenca Pina Moreira; Barbosa, Graciele Vieira; Fischer, Eliane Kujat; da Silva, Lucas Lemos; Li, Máximo Siu; de Moura, Ana Paula [UNESP]; Cavalheiro, Alberto Adriano (Trans Tech Publications, 2018)
Lead zirconate titanate (PZT) is a wide versatile material applied in several electronic devices. Some of dielectric and piezoelectric characteristics depend on phase formation, crystallization and composition. In this work, we prepare PZT powder samples with different compositions by the Polymeric Precursor Method, which were thermally treated at very low temperatures in order to get amorphised powder samples. The zirconium-rich PZT6040 sample showed a significant uptake in photoluminescent emission between 320 ºC and 350 ºC, followed by a slightly increasing in bandgap energy. In spite of the bandgap energy posses the typical value for several structurally disordered semiconductors, these effects were associated to the coexistence of pyrochlore and tetragonal perovskite phases in that referred conditions.
Keywords: Optical gap; Photoluminescence; PZT